ACTIVATION OF CONTEXTUAL AND CATEGORY INFORMATION WITH LINE DRAWING RECOGNITION MEMORY TASKS - Navalón Vila, Conrado; Pérez Sánchez, Miguel Angel; López García, Juan José (Anales de Psicología / Annals of Psychology)
This work is included within recent short term memory theories. Short term memory is understood as temporary retention of information, that is, the part of permanent memory which is temporarily activated from a critical threshold and that can be recognized and manipulated by active cognitive processes. We begin from the assumption that in recognition memory tasks with significant materials, subjects activate and process not only the stimulus information but also category information related to input and context information present in the stimulus situation. Two experiments are made with YES/NO test of recognition memory, introducing variations both in the category relations between study and new stimuli Results confirm the initial hypothesis.